Use of the Blockchain System and its Traceability in Agribusiness - Melotti, Leonardo Marcondes Domingues (2023)
The food production and consumption model runs through a large logistics chain until it reaches the final consumer. The use of the supply chain provides for all movement and storage activities, from the moment a product is acquired until the moment of consumption, at a reasonable cost. Every day, the consumer becomes more demanding about the details of this chain. This fact falls on the objectives of this work to demonstrate that the use of Blockchain technology can contribute to the generation of value in the food chain. To achieve this objective, a bibliographic study was carried out in academic texts, related to the theme, Blockchain and agribusiness, seeking to understand how technology can add more value in the food chain. In the end, it was found that the traceability and transparency of commodity-oriented transactions result in increased user confidence. The fact that traceability is accessible and the protection that blockchain cryptography guarantees, avoid misconduct and there is a decrease in the existence of flawed data or that does not correspond to reality.